2014
DOI: 10.5152/tud.2013.036
|View full text |Cite
|
Sign up to set email alerts
|

The effect of preoperative intravenous dexketoprofen trometamol on postoperative pain in minor outpatient urologic surgery

Abstract: Objective: The aim of this prospective double-blind randomized study was to compare the effectiveness of preoperative dexketoprofen trometamol for acute postoperative pain in patients undergoing minor outpatient urologic surgery. Material and methods:Sixty male patients (ASA I and II) undergoing varicocelectomy and testicular sperm extraction (TESE) with standard laryngeal mask airway (LMA) anesthesia were randomly divided into two groups. Patients in Group I (n=30) received 50 mg of dexketoprofen trometamol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Eight studies reported lower opioid consumption and postoperative pain, as well as a longer time requiring a second dose of the drug, favoring preoperative administration of DEX. One study (Bolat et al, ) reported no difference in the same comparison previously described. However, this study did not report the total data of the study.…”
Section: Qualitative Synthesismentioning
confidence: 63%
See 3 more Smart Citations
“…Eight studies reported lower opioid consumption and postoperative pain, as well as a longer time requiring a second dose of the drug, favoring preoperative administration of DEX. One study (Bolat et al, ) reported no difference in the same comparison previously described. However, this study did not report the total data of the study.…”
Section: Qualitative Synthesismentioning
confidence: 63%
“…of DEX (Eroglu, Durmus, & Kiresi, ; Esparza‐Villalpando et al, ; Iohom, Walsh, Higgins, & Shorten, ; Kara, Tuncer, Erol, & Reisli, ; Kesimci, Gümüs, & Kanbak, ), while the other studies employed intravenous (i.v.) administration (Atalay, Dogan, & Kizilkaya, ; Bolat, Erhan, & Deniz, ; Çağiran, Eyigör, & Sezer, ; Gelir, ; Gülhaş et al, ; Kadıoğlu, Tüker, Gurbet, Demirci, & Hülagü, ; Kelsaka, Guldogus, & Cetinoglu, ; Sagiroglu, ; Ozer et al, ). Eight studies utilized DEX 50 mg (Atalay et al, ; Bolat et al, ; Çağiran et al, ; Gelir, ; Gülhaş et al, ; Kadıoğlu et al, ; Kelsaka et al, ; Ozer et al, ), while the remaining studies evaluated DEX 25 mg (Esparza‐Villalpando et al, ; Iohom et al, ; Kara et al, ; Kesimci et al, ; Ozer et al, ; Sagiroglu, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations